Did export promotion help firms weather the crisis? - Johannes Van Biesebroeck; Jozef Konings; Christian Volpe Martincus (National Bank of Belgium, 2016)
In the global recession of 2009, exports declined precipitously in many countries. We illustrate with firm-level data for Belgium and Peru that the decline was very sudden and almost entirely due to lower export sales by existing exporters. After the recession, exports rebounded almost equally quickly and we evaluate whether export promotion programs were an effective tool aiding this recovery. We show that firms taking advantage of this type of support did better during the crisis, controlling flexibly for systematic differences between supported and control firms. The primary mechanism we identify is that supported firms are generally more likely to survive on the export market and, in particular, are more likely to continue exporting to countries hit by the financial crisis.
Keywords: F13; F14; F44; 330; trade promotion; trade policy; Great Recession; business cycles; Finanzkrise; Handelseffekt; Außenwirtschaftsförderung; Außenhandel; Belgien; Peru